Divide x+p+1 by p(p+1)
Answers
Answered by
0
Answer:
P(x) is non –zero polynomial and P(1+x)=P(1−x) for all x
Differentiate w.r.t x
P
′
(1+x)=−P
′
(1−x)
Put x=0,P
′
(1)=−P
′
(1)
⇒P
′
(1)+P
′
(1)=0
⇒2P
′
(1)=0
⇒P
′
(1)=0
and P(1)=0⇒P(x) touches the x− axis at x=1
⇒P(x)=(x−1)
2
Q(x)
⇒m=2 such that (x−1)
m
divides P(x) for all such P(x
Similar questions
Chemistry,
6 months ago
Computer Science,
6 months ago
Social Sciences,
6 months ago
Math,
1 year ago
English,
1 year ago
Social Sciences,
1 year ago
Computer Science,
1 year ago